2006
DOI: 10.1002/jbm.b.30578
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid layer seals the cementum/4‐META/MMA‐TBB resin interface

Abstract: Although 4-META/MMA-TBB resin has adhesive properties to dentin, and has been clinically used for the bonding treatment of vertically fractured roots and apicoectomy, there has not been any investigation on the adhesion of 4-META/MMA-TBB resin to cementum. The purpose of this in vitro study was to evaluate the bonding and the sealing ability of 4-META/MMA-TBB resin to cementum. Bovine root cementum and dentin surfaces were treated with a citric acid and ferric chloride solution, and the 4-META/MMA-TBB resin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Despite morphological differences between cementum, dentin and bone, they are composed mainly of collagen and hydroxiapatite (5). Generally, cementum is least mineralized when compared to the others hard tissues: enamel, dentin and bone (15), and is less hard and more permeable compared with enamel and dentin (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite morphological differences between cementum, dentin and bone, they are composed mainly of collagen and hydroxiapatite (5). Generally, cementum is least mineralized when compared to the others hard tissues: enamel, dentin and bone (15), and is less hard and more permeable compared with enamel and dentin (6).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the margins of many adhesive restorations on the root surface are thought to be positioned in cementum or cervical outer dentin (2). While the bond to dentin is important, that to cementum is also critical to prevent microleakage and bacteria gaining access to the underlying dentin (5). The root cementum has high organic content and predominantly consists of cross-linked collagen structure.…”
Section: Introductionmentioning
confidence: 99%
“…The collagen fibrils that are not enveloped by resin may become susceptible to water degradation in the long-term. 22,18,9 Even so, further investigations are required to determine the durability of resin bonds to human cementum.…”
Section: Discussionmentioning
confidence: 99%
“…5 Cementum hybridization is related to structure, chemical composition and bonding efficacy of human cementum, which has a lower packing density than dentine. 8 Cementum is a specialized and mineralized tissue mm thick), 9 pale yellow with dull surface. The principal inorganic component is hydroxyapatite while other forms of calcium are also present.…”
Section: Introductionmentioning
confidence: 99%
“…C&B ® ), is widely utilized as a dental adhesive in Japan. Previous studies have reported its excellent adhesive properties with tooth hard tissues, including enamel [11], dentin [12] and cementum [13], and a moderate biocompatibility with dental pulp [14] and periodontal tissue [15,16]. Furthermore, several studies in recent years have reported its bond strength to bone [17,18].…”
Section: Introductionmentioning
confidence: 99%